Hsa_circ_0018909 promotes non-small cell lung cancer by directly regulating hsa-miR-513b-5p - Liu, Qi; Yu, Yong-Kui; Li, Hao-Miao; Wang, Wei; Xu, Jing (Frontiers in Oncology, 2025)
BackgroundCircular RNAs (circRNAs) regulate gene expression by functioning as competing endogenous RNAs (ceRNAs) and are increasingly recognized for their involvement in cancer progression. Hsa_circ_0018909 is upregulated in non-small cell lung cancer (NSCLC); however, its functional role and underlying mechanisms remain poorly understood. This study aimed to investigate the role of hsa_circ_0018909 and its downstream regulatory axis in NSCLC.MethodsDifferentially expressed circRNAs were identified from the GSE101586 dataset. The expression levels of hsa_circ_0018909 and hsa-miR-513b-5p were validated in NSCLC tissues and cell lines. CircBase and UCSC were used to determine the genomic origin of hsa_circ_0018909, and its subcellular localization was examined using fluorescence in situ hybridization. The interaction between hsa_circ_0018909 and hsa-miR-513b-5p was predicted with TargetScan and verified through dual-luciferase reporter assays. Functional assays, including CCK-8, colony formation, Transwell migration/invasion, and subcutaneous tumor formation in nude mice, were conducted to evaluate the effects of hsa_circ_0018909. Rescue experiments and Western blot analyses were performed to identify downstream targets and elucidate the underlying regulatory mechanisms.ResultsAmong the five upregulated circRNAs identified, only hsa_circ_0018909 consistently showed high expression in NSCLC tissues and cell lines and was associated with shorter overall and disease-free survival. Hsa_circ_0018909 was primarily localized in the cytoplasm. Overexpression of hsa_circ_0018909 enhanced the proliferation, migration, and invasion of NSCLC cells, while its knockdown produced the opposite effects. Hsa-miR-513b-5p mimics attenuated the oncogenic effects of hsa_circ_0018909, whereas inhibition of hsa-miR-513b-5p reversed the suppressive effects of hsa_circ_0018909 knockdown. Mechanistically, hsa_circ_0018909 directly binds to hsa-miR-513b-5p and negatively regulates its expression. Malate dehydrogenase 1 (MDH1) was identified as a direct downstream target of hsa-miR-513b-5p. Rescue experiments confirmed that MDH1 mediates the tumor-promoting effects resulting from hsa-miR-513b-5p inhibition in NSCLC cells.ConclusionHsa_circ_0018909 is significantly upregulated in NSCLC and promotes tumor progression by sponging hsa-miR-513b-5p, thereby indirectly upregulating its downstream target, MDH1. These findings suggest that the hsa_circ_0018909/miR-513b-5p/MDH1 axis may represent a potential therapeutic target for NSCLC.